The Use of an Alternative Extraoral Periapical Technique for Patients with Severe Gag Reflex - Mauro Henrique Chagas e Silva; Marcelo Santos Coelho; Mariane Floriano Lopes Santos; Carolina Oliveira de Lima; Celso Neiva Campos (Hindawi Limited, 2016)
Gag reflex is a physiologic mechanism that promotes contraction of the muscles of the tongue and pharyngeal walls. Different factors, including intraoral radiographic films and sensors, may trigger this reflex. Patients with severe gag reflex may not be able to tolerate the presence of intraoral radiographic films or sensors during root canal therapy (RCT). This factor may prevent an appropriate intraoral radiograph, which is important in RCT. Different approaches have been used to facilitate dental procedures in patients suffering from severe gag reflex. The use of an extraoral radiographic technique is an alternative method to obtain working length confirmation in patients with severe gag reflex. In this report of 2 cases, the use of an extraoral radiographic technique as an alternative approach during RCT in patients with severe gag reflex associated with phobic behavior and trismus was successfully demonstrated.